2017
DOI: 10.1002/ldr.2733
|View full text |Cite
|
Sign up to set email alerts
|

Developing Soil Conservation Strategies with Technical and Community Knowledge in a Degrading Sub‐Humid Mountainous Landscape

Abstract: Worldwide, soil erosion has greatly decreased agricultural productivity and continues unabatedly despite decades of developing sustainability and soil conservation strategies. Current strategies need integrated interdisciplinary perspectives to develop more effective measures, especially in degrading mountainous landscapes where rising sediment concentrations persist. By comparing spatio‐temporal field observations and community perceptions with the Geographic Information System (GIS)‐based universal soil loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 88 publications
0
9
0
Order By: Relevance
“…The final group of articles documents examples of successful cooperation between scientists and nonacademic stakeholders in research and management planning. Guzman et al (2018) used a combination of hydrological and erosion monitoring, soil erosion modelling, and participatory approaches (group discussion, transect walk, participatory mapping) to evaluate the most suitable methods for soil conservation planning in Ethiopia. Waltner et al (2018) used reports from a farm management system to assess the precision of model‐based soil erosion risk maps in Hungary.…”
Section: Timeliness and Relevance Of The Issuementioning
confidence: 99%
“…The final group of articles documents examples of successful cooperation between scientists and nonacademic stakeholders in research and management planning. Guzman et al (2018) used a combination of hydrological and erosion monitoring, soil erosion modelling, and participatory approaches (group discussion, transect walk, participatory mapping) to evaluate the most suitable methods for soil conservation planning in Ethiopia. Waltner et al (2018) used reports from a farm management system to assess the precision of model‐based soil erosion risk maps in Hungary.…”
Section: Timeliness and Relevance Of The Issuementioning
confidence: 99%
“…Organized implementation of soil and water conservation (SWC) started in the 1970s after land degradation was identified as the main reason causing famine during periods of drought (Bewket & Sterk, ). Short‐term studies labeled these works as ‘impressive’ but studies that evaluated them over a longer period revealed that while performing well in the semi‐arid regions by increasing water retention (Herweg & Ludi, ; Nyssen et al, ), effectiveness was minimal in the subhumid and humid monsoonal climates (Guzman et al, ). Despite previous experience, in 2010, the government of Ethiopia implemented an extensive nationwide ecological restoration program, which was aimed at doubling agricultural productivity and on enhancing infiltration (Dagnew et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, technical solutions for conserving soil will not perform optimally without local input. Farmers have considerable local knowledge and skills that will make any of the proposed practices more suitable and appropriate to their own conditions (Guzman, Tilahun et al, ; Pretty & Shah, ). By strengthening local organizations through participatory processes, practices will better function because detailed information on alternative site‐specific designs for policymakers are currently lacking and these practices will be more sustainable because of ownership by the community (Pretty & Shah, ; Ayele et al, ).…”
Section: Improving Watershed Management Practices In the Humid Regionmentioning
confidence: 99%
“…In Ethiopia, poorly placed soil and water conservation practices are responsible for one third of the erosion loss (Hagmann, ; Haile, Herweg, & Stillhardt, ). This reveals an ongoing and unaddressed gap in our understanding of hydrology, water management, and soil erosion in developing countries and around the world (Forsyth, ; Guzman, Tilahun et al, ; Hoben, ; Stocking, ).…”
Section: Introductionmentioning
confidence: 99%